Standardization of Woodcock battery for language proficiency - Tapia Mendieta, Violeta (1998)
We have been elaborated percentils procedures and Z points for a scholastic population of second to sixth degree of Lima metropolitan, belonging to particular and state educational centers. The variables had in account are age and scholastic degree. Previously U was accomplished the cultural adjustment of some articles and with psichometric analysis being verified the validity and reliability of the instrument.